1998
DOI: 10.1902/jop.1998.69.2.165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on Individuals With Minimal Periodontal Destruction

Abstract: Recent studies have demonstrated that smoking is associated with periodontal destruction. The majority of these studies have focused on periodontal disease groups with moderate or severe periodontal destruction. Additionally, there have been few reports investigating the relationship between smoking and gingival recession. The goal of this report was to investigate the effect of smoking on periodontal destruction and recession in subjects with minimal or no interproximal attachment loss. This is a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
2
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 22 publications
12
63
2
7
Order By: Relevance
“…The research is not conclusive with Gunnsolley et al [67] demonstrating a strong association between smoking and both attachment loss and recession in subjects who have minimal or no periodontal disease. Other data do not support the hypothesis that smokers not susceptible to periodontal disease are at an increased risk for the development of gingival recession [68].…”
Section: Lesion Localisationmentioning
confidence: 65%
“…The research is not conclusive with Gunnsolley et al [67] demonstrating a strong association between smoking and both attachment loss and recession in subjects who have minimal or no periodontal disease. Other data do not support the hypothesis that smokers not susceptible to periodontal disease are at an increased risk for the development of gingival recession [68].…”
Section: Lesion Localisationmentioning
confidence: 65%
“…Frequent tooth-brushing and poor oral health were significant risk factors in epidemiological studies on gingival recession in adults 6,18) . Smoking was also a significant risk factor for periodontal disease 2,9) . In this study, living in an institution, number of present teeth and smoking were significant risk factors for gingival recession.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, after treatment, a greater degree of recession occurred among the non-smokers compared with the smokers. In the description of the appearance of smokers' periodontal condition, and in studies looking cross-sectionally at smokers, a commonlv noted feature is the level of recession, which is often noted as worse in smokers than in non-smokers (Martinez-Canutt et a., 1995;Gunsolley et al, 1998 (Cortellini et al, 1996. Trombelli andScabia, 1997;, and other investigators, when using regenerative procedures with allografts, have also found smoking to be detrimental to healing (Luepke et al, 1997;Rosen et al, 1996) Haas et al (I 996) Fibroblasts are an important cell in the periodontal heal-REFERENCE ing response, and Raulin et al (1988) has reported an impaired function of fibroblasts in smokers.…”
Section: Discussionmentioning
confidence: 99%